2016
DOI: 10.1021/acs.inorgchem.6b01524
|View full text |Cite
|
Sign up to set email alerts
|

Phosphenium Versus Pro-Phosphide Character of P-tert-butyl-dicyclopropeniophosphine: Zwitterionic Palladate Complexes of a Dicationic Phosphido Ligand

Abstract: With the view to enhancing the unique coordinating ability of the known phenyl-tetrakis(diisopropylamino)dicyclopropeniophosphine (Ph-DCP), replacement of the phenyl substituent by a tert-butyl substituent was envisaged. Both α-dicationic R-DCP phosphines, with R = Ph and Bu, were prepared in 54%-55% yield by substitution of RPCl with two equivalents of bis(diisopropylamino)-dicyclopropenylidene (BAC) and metathesis with NaBF. This method is implicitly consistent with the representation of R-DCPs as BAC-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Simultaneously, Weigand reported the preparation of coinage metal complexes of a much more bulky, asymmetrically substituted variant . Remarkably it has recently been shown that a dicationic phosphine may act as a cyclopropenylidene‐stabilised P I pro‐ligand in the presence of excess PdCl 2 by heterolytic cleavage of a tert ‐butyl group . Considering the intensifying interest in this field and in the field of cationic ligands in general, we now report the isolation of various cationic metal–carbonyl complexes of the NHC‐stabilised phosphorus(I) ligand [L] + ([L] + =[bis(1,3,4,5‐tetramethylimidazol‐2‐ylidene)phosphanide] + ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Simultaneously, Weigand reported the preparation of coinage metal complexes of a much more bulky, asymmetrically substituted variant . Remarkably it has recently been shown that a dicationic phosphine may act as a cyclopropenylidene‐stabilised P I pro‐ligand in the presence of excess PdCl 2 by heterolytic cleavage of a tert ‐butyl group . Considering the intensifying interest in this field and in the field of cationic ligands in general, we now report the isolation of various cationic metal–carbonyl complexes of the NHC‐stabilised phosphorus(I) ligand [L] + ([L] + =[bis(1,3,4,5‐tetramethylimidazol‐2‐ylidene)phosphanide] + ).…”
Section: Introductionmentioning
confidence: 90%
“…[77] Remarkably it has recentlyb een shown that ad icationic phosphine may act as ac yclopropenylidene-stabilised P I pro-ligand [78] in the presenceo fe xcess PdCl 2 by heterolytic cleavage of a tert-butyl group. [79] Considering the intensifying interesti nt his field and in the field of cationic ligands in general, we now report the isolation of various cationic metal-carbonyl complexes of the NHC-stabilised phos-…”
Section: Introductionmentioning
confidence: 98%
“…1b, 14 An alternative route for the synthesis of ligands 15, which utilizes the reaction of chlorophosphines with bis(diisopropylamino)dicyclopropenylidene 18, was subsequently described. 15 Although both 16 and 17 are catalytically competent in alkyne hydroarylation reactions, the Scheme 2 Effect of the cationic phosphine in a) hydroformylation of 1-octene, b) Sonogashira coupling with acid chlorides, and c) cycloisomerization of allendienes. Reagents and conditions: (i) 4, 5, or6 (0.2 mol%), [Rh(CO) 2 acac] (0.1 mol%), CO/H 2 (1:1), 10 bar, 100 °C; (ii) 7 or 8 (0.5 mol%), CuI (1 mol%), Et 3 N, THF, RT; (iii) [LAuCl]…”
Section: Scheme 3 General Methods For the Synthesis Of Bis(imidazolio)phosphinesmentioning
confidence: 99%
“…Analogy between mono- ( A + – B + ) and dicationic phosphines ( A 2+ – B 2 + ) , (left) vs mono- ( C + ) and dicationic NHCs 1 2+ (right).…”
Section: Introductionmentioning
confidence: 99%